Documento e musealização: entretecendo conceitos - Maria Lucia de Niemeyer Matheus Loureiro; José Mauro Matheus Loureiro (Midas: Museus e Estudos Interdisciplinares)
The text addresses musealisation as a process (or set of processes) through which some objects are deprived of their original function and, after gaining new meanings, acquire the role of document. The text emphasizes the informational nature of the processes of musealisation and presents reflections on the notion of the document throughout the twentieth century, highlighting the expansion of the concept beyond the writing and pioneering contribution of Paul Otlet.